A Bayesian Approach to Setting the Release Limits for Critical Quality Attributes. (3rd July 2018) - Yu, Binbing; Zeng, Lingmin; Yang, Harry
ABSTRACT: To ensure the safety, efficacy, and quality, regulatory authorities require that multiple critical quality attributes of a drug must conform to certain specification limits. Manufacturers must establish a set of release limits for drug substance or final drug product batches, so that the released drug product batches remain within the specification limits during the whole shelf-life. Various statistical methods have been proposed to determine the release limits such that the probability of out-of-specification at the end of shelf-life will be controlled under a desirable level. Stringent release limits result in tight quality control of the drug quality, thus protecting consumer's risk. On the other hand, overly tight release limits may cause unnecessary rejection of a good batch of drug substance or drug product, resulting increased manufacturer's risk. Therefore, the release limits should be constructed to control both the consumer's risk of releasing a bad batch to the market and the manufacturer's risk of rejecting a good batch. Since the pharmaceutical release procedure is complex and usually consists of many quality-control steps, a holistic strategy for risk management shall be established. In this article, we propose a Bayesian approach for determining the release limits for critical quality attributes to keep the balance of both types of risks in the situation of multiple process steps and storage conditions. The proposed method is easy to implement and can be used to control the risks of intermediate steps as well as the holistic risk of a multi-step drug release process.